1996
DOI: 10.1159/000129464
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic Ischemia Induces Major Histocompatibility Complex Class I Expression in Hepatocytes

Abstract: The hepatic expression of major histocompatibility complex (MHC) antigens is normally limited. However aberrant expression may occur in cholestatic diseases or following liver transplantation. The aim of this work was to investigate the effect of normothermic ischemia on hepatocellular MHC expression. Temporary (90-min) normothermic ischemia of the liver was induced in inbred rats. There was a significant elevation of aspartate aminotransferase and alanine amino-transferase levels after ischemia, rising to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…In a previous study, we showed that severe IRI to hepatocytes, as reflected by a high peak alanine aminotransferase, was also an important risk factor for NAS development . Interestingly, Gugenheim et al demonstrated an upregulation of hepatic class I antigen expression after a period of normothermic ischemia in a rat model …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed that severe IRI to hepatocytes, as reflected by a high peak alanine aminotransferase, was also an important risk factor for NAS development . Interestingly, Gugenheim et al demonstrated an upregulation of hepatic class I antigen expression after a period of normothermic ischemia in a rat model …”
Section: Discussionmentioning
confidence: 99%
“…10 Interestingly, Gugenheim et al demonstrated an upregulation of hepatic class I antigen expression after a period of normothermic ischemia in a rat model. 37 It could therefore be expected that a relation exists between IRI, the presence of antibodies against donor HLA antigens expressed on hepatocytes and biliary epithelium and bile duct complications, DSA are related to an inferior clinical outcome after OLT. 7,9 Sensitivity analysis was performed in the current study for MFI>1000 with similar outcomes.…”
Section: Discussionmentioning
confidence: 99%